2014
DOI: 10.3390/rs6065107
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Different Wheat Rust Disease Symptoms on Vegetation Indices Using Hyperspectral Measurements

Abstract: Spectral Vegetation Indices (SVIs) have been widely used to indirectly detect plant diseases. The aim of this research is to evaluate the effect of different disease symptoms on SVIs and introduce suitable SVIs to detect rust disease. Wheat leaf rust is one of the prevalent diseases and has different symptoms including yellow, orange, dark brown, and dry areas. The reflectance spectrum data for healthy and infected leaves were collected using a spectroradiometer in the 450 to 1000 nm range. The ratio of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 36 publications
1
59
0
2
Order By: Relevance
“…In fact, other authors identified spectral bands in the red and green regions as candidates to improved discrimination between healthy and diseased plants, at leaf level (Ashourloo et al, 2014;Mahlein et al, 2013). However, the dataset analysed here concerns only one acquisition date and spectral data at the plot level corresponded to all spectral signatures acquired, including areas…”
Section: Results and Conclusionmentioning
confidence: 99%
“…In fact, other authors identified spectral bands in the red and green regions as candidates to improved discrimination between healthy and diseased plants, at leaf level (Ashourloo et al, 2014;Mahlein et al, 2013). However, the dataset analysed here concerns only one acquisition date and spectral data at the plot level corresponded to all spectral signatures acquired, including areas…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Studies have shown that once several sensitive bands are confirmed, the wheat powdery mildew could be diagnosed precisely by calculating a vegetation index (Mahlein et al, 2012). Table 2 shows several disease vegetation indexes (Devadas et al, 2009;Naidu et al, 2009;Ashourloo et al, 2014c). In order to enhance the disease features recognition; this study also used the red edge parameters, including the slope of the red edge, red edge position and the red edge area (Table 2) (Zhang et al, 2012).…”
Section: Band Operationmentioning
confidence: 99%
“…However, the generalization and robustness of the models have to be verified in the scale of field with the data across crop varieties (Devadas et al, 2009;Ashourloo et al, 2014a;Huang et al, 2014). Up to now, there are still few literatures focused on crop disease recognition and assessment in the scale of crop canopy and field (Ashourloo et al, 2014b). Devadas et al (2009) found that healthy, diseased and shadowed leaves, wheat ear, wheat stems and soil constitutes a complex environmental background for wheat disease diagnosis in the field (Devadas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations